In vitro propagation of Citrus hystrix and assessment of genetic uniformity using RAPD markers - Eng, Wee Hiang (2013)
Recent studies in Citrus hystrix largely focused on its usage in citriculture, pharmaceutical and nutritional values. This newly emerged plant urgently needs biotechnological studies especially on the establishment of its micropropagation protocol. The objectives of this study are (a) to develop an efficient micropropagation system using various juvenile explants of C. hystrix seedlings, (b) to elucidate genetic uniformity of plantlets derived from the juvenile explants using RAPD markers and (c) to develop an effective sterilization technique and induction of multiple shoot formation from nodal segments of mature field grown C. hystrix. In vitro seedling and field-grown mature C. hystrix was used as source of explants to assess regeneration capability. In this study, various concentrations of BAP were assessed to determine the optimum concentration for regeneration. Leaves abscission occured during regeneration stage. To overcome the problem, Ca-gluconate and silver nitrate were amended into medium containing optimized concentration of BAP. In rooting stage, continuous auxin treatment and auxin pulse treatment were tested to determine efficient rooting method. Types of potting mixture were assessed to determine the best potting mixture for survival of deflasked in vitro plantlets. For sterilization study using field-grown mature plant, different types and combination of antibiotics were tested to reduce latent bacterial contamination. Medium with combination of BAP, GA3 and AgNO3 were tested to determine the best medium for shoot regeneration for field-grown mature plant. RAPD markers were used for screening uniformity of regenerants from in vitro seedling. The optimum regeneration medium for shoot tip was MS medium + 2.22 μM BAP + 4 mM Ca-glu + 20 μM AgNO3 + 30 g/L sucrose, inducing four shoots per explant. For epicotyls, hypocotyls, primary roots and cotyledons, the optimum regeneration medium was MS medium + 2.22 μM BAP + 10 μM AgNO3 + 30 g/L sucrose which induced five, four, three and two shoots, respectively. For in vitro rooting, auxin pulse treatment with 9840 μM IBA in MS medium for 16 h prior to transfer to MS medium + 20 μM AgNO3 produced significantly the highest number of roots (2 roots) and highest rooting percentage (87.50%). In the acclimatization study, medium consisting of soil : Peatgro : sand (1 : 1 : 1) was the best attaining a survival percentage of plantlets at 83.33%. Genetic stability of the plantlets was assessed using RAPD markers. Most of the plantlets were identical to the mother plant based on RAPD banding pattern. Eighteen out of twenty samples had Jacaard’s similarity coefficient of 1.0000 indicating 90% of the regenerants were likely to be clones. For effective sterilization of nodal segments derived from mature field grown C. hystrix the use of 500 mg/L cefotaxime as part of the surface sterilization procedure successfully reduced percentage of latent bacterial contamination and resulted in significantly the highest survival percentage (61.25%) after eight weeks of culture. The optimised regeneration medium for nodal segments of mature plants of C. hystrix was MS medium + 2.22 μM BAP + 20 μM AgNO3 + 30 g/L sucrose inducing three shoots per explant. Through this study, an efficient micropropagation system has been developed that could provide a mean for mass propagation, and as a tool in genetic modification and in vitro germplasm conservation of C. hystrix.